Terminal 6q deletions cause brain malformations, a phenotype mimicking heterozygous DLL1 pathogenic variants: A multicenter retrospective case series. (11th December 2021) - Lesieur‐Sebellin, Marion; Till, Marianne; Khau Van Kien, Philippe; Herve, Bérénice; Bourgon, Nicolas; Dupont, Céline; Tabet, Anne‐Claude; Barrois, Mathilde; Coussement, Aurélie; Loeuillet, Laurence; Mousty, Eve; Ea, Vuthy; et al.
Abstract: Objective: Terminal 6q deletion is a rare genetic condition associated with a neurodevelopmental disorder characterized by intellectual disability and structural brain anomalies. Interestingly, a similar phenotype is observed in patients harboring pathogenic variants in the DLL1 gene. Our study aimed to further characterize the prenatal phenotype of this syndrome as well as to attempt to establish phenotype‐genotype correlations. Method: We collected ultrasound findings from 22 fetuses diagnosed with a pure 6qter deletion. We reviewed the literature and compared our 22 cases with 14 fetuses previously reported as well as with patients with heterozygous DLL1 pathogenic variants. Results: Brain structural alterations were observed in all fetuses. The most common findings (>70%) were cerebellar hypoplasia, ventriculomegaly, and corpus callosum abnormalities. Gyration abnormalities were observed in 46% of cases. Occasional findings included cerebral heterotopia, aqueductal stenosis, vertebral malformations, dysmorphic features, and kidney abnormalities. Conclusion: This is the first series of fetuses diagnosed with pure terminal 6q deletion. Based on our findings, we emphasize the prenatal sonographic anomalies, which may suggest the syndrome. Furthermore, this study highlights the importance of chromosomal microarray analysis to search for submicroscopic deletions of the 6q27 region involving the DLL1 gene in fetuses with these malformations. Key points: What's already known about this topic? The prenatal ultrasound features of terminal 6q deletions are not well known What does this study add? We report on a series of 22 fetuses. Cerebellar hypoplasia, ventriculomegaly, and anomalies of the corpus callosum are the most frequent ultrasound findings detected in the fetuses. Furthermore, this study highlights the crucial role of the DLL1 gene in brain anomalies and underlines the importance of chromosomal microarray analysis to search for 6q27 microdeletion involving this gene